Preparation and Optimisation of Cross-Linked Enzyme Aggregates Using Native Isolate White Rot Fungi Trametes versicolor and Fomes fomentarius for the Decolourisation of Synthetic Dyes - Vršanská, Martina; Voběrková, Stanislava; Jiménez Jiménez, Ana María; Strmiska, Vladislav; Adam, Vojtěch (International journal of environmental research and public health, 2017)
The key to obtaining an optimum performance of an enzyme is often a question of devising a suitable enzyme and optimisation of conditions for its immobilization. In this study, laccases from the native isolates of white rot fungi Fomes fomentarius and/or Trametes versicolor, obtained from Czech forests, were used. From these, cross-linked enzyme aggregates (CLEA) were prepared and characterised when the experimental conditions were optimized. Based on the optimization steps, saturated ammonium sulphate solution (75 wt.%) was used as the precipitating agent, and different concentrations of glutaraldehyde as a cross-linking agent were investigated. CLEA aggregates formed under the optimal conditions showed higher catalytic efficiency and stabilities (thermal, pH, and storage, against denaturation) as well as high reusability compared to free laccase for both fungal strains. The best concentration of glutaraldehyde seemed to be 50 mM and higher efficiency of cross-linking was observed at a low temperature 4 °C. An insignificant increase in optimum pH for CLEA laccases with respect to free laccases for both fungi was observed. The results show that the optimum temperature for both free laccase and CLEA laccase was 35 °C for T. versicolor and 30 °C for F. fomentarius. The CLEAs retained 80% of their initial activity for Trametes and 74% for Fomes after 70 days of cultivation. Prepared cross-linked enzyme aggregates were also investigated for their decolourisation activity on malachite green, bromothymol blue, and methyl red dyes. Immobilised CLEA laccase from Trametes versicolor showed 95% decolourisation potential and CLEA from Fomes fomentarius demonstrated 90% decolourisation efficiency within 10 h for all dyes used. These results suggest that these CLEAs have promising potential in dye decolourisation.
Keywords: Coloring Agents; Azo Compounds; Temperature; Trametes; Polyporales; Laccase; Color; glutaraldehyd; lakasa; Glutaral; reagencia zkříženě vázaná; Rosaniline Dyes; Ammonium Sulfate; katalýza; síran amonný; enzymy imobilizované; Bromthymol Blue; barvicí látky; bromthymolová modř; barva; azosloučeniny; Catalysis; Cross-Linking Reagents; teplota; Enzymes, Immobilized; rosanilinová barviva